Ecology, ecosystem & conservation biology - Ashraf, Muhammad Aqeel; Khan Chowdhury, Ahmed Jalal (Triveni Enterprises, 2019)
Ecology is the study of the interaction between organisms and their environment. To fulfill the food requirements of increasing population, human activities are affecting the ecosystem. It has never been extra important to comprehend what regulates the dispersal and richness of species, how they intract with each other and their environment, and how biodiversity rejoins to threats by change in climate, invasive species, over-exploitation and destruction of habitat. Issues arising due to climate change, understanding the ecosystem, and the measures required to sustain Earth's life-support systems has become progressively important. In this evolutionary process, human activities have played a prominent role, and those who study vegetation cannot afford to neglect this aspect. Conversion of natural habitats into industrial and agricultural landscapes, and finally into tainted land, is the major influence of humans on the natural environment, posing a great threat to biodiversity. Restoration of ecosystem is an emerging discipline which provides a more suite of tools for the recovery of degraded lands. Restoration of ecology offers a crucial accompaniment to nature reserves as a way for the preservation of biodiversity. An unified understanding of human population growth and changes in agricultural practices with natural recovery processes and restoration ecology offers hope for the future of the environment. Even though ecologists have documented the role of history and historical legacy concept in determining present-day ecological systems, few international conservation assessments consider time scales more than 50 years. Conservation biology is prearranged management of natural resources and natural balance retention, diversity and evolutionary processes in the environment. Conservation strategies in a rapidly changing world need to consider the dynamic biological processes of species and their interactions with their environment: it is here that insights from long-term ecology can guide conservation.